General Equilibrium Under Shortage : A Generalized Barro-Grossman Model - Osband, Kent (IMF Working Papers; Working Paper ;, 1991)
In several recent articles, the Barro-Grossman model of general equilibrium under shortage has been modified to incorporate money demand and alternative retail sales mechanisms. This paper extends this work to allow for spillovers in deficit goods markets (modeled as feedback of black market prices on the real value of nominal money balances). Comparative statics analysis confirms the conventional view, recently challenged in the literature, that government expenditure in a shortage economy tends to reduce output. The conventional view associating shortage with higher savings is, however, substantially qualified. The model appears to be more consistent than previous models with the available empirical evidence, and offers insights into the consequences of price and monetary reform in shortage economies.